Conceptualizing the enhancement of employability among undergraduates in work-based learning settings - Anas, Ilyana; Hamzah, Siti Raba'ah (Faculty of Educational Studies, Universiti Putra Malaysia, 2017)
The ubiquity of employability issues is becoming crucial in human resource development perspectives worldwide. The 2u2i program is designed to fulfil the needs of the graduate by offering flexible education in higher education as well as employability enhancement This paper proposes a conceptual model of factors that could enhance employability in work-based learning (WBL) settings. The conceptual model is based on an extensive review of past research on WBL and employability using the CareerEDGE model. To conduct the literature review, we used keywords such as employability, work-based learning, employability skills and internship. From the literature reviewed, six elements of employability have been identified which are career development learning, experience, degree subject knowledge, emotional intelligence, generic skills, and social support. The framework offers a number of propositions, which explain the proposed model of employability. The paper has adopted 5 elements from the CareerEDGE model and 1 element has been derived from literature review added to the model. Further research is suggested to test and validate the framework to provide empirical evidence. Upon model validation, the paper could offer practical interventions for HRD practitioners and academicians.